Communication for the win: task benefits of coach confirmation in collegiate athletics. Issue 5 (19th October 2020) - Cranmer, Gregory; Ash, Erin; Fontana, Joseph L.; Mikkilineni, SaiDatta
ABSTRACT: There is a heuristic and practical need to identify prosocial coaching behaviors that benefit both the relational climates on sports teams and team performance. This study considers the influence of coaches' use of confirmation (i.e., consisting of acceptance and challenge) on student-athletes' self-confidence, team task cohesion, and team winning. Data collected from 117 Division-I student-athletes, who participated in team sports, partially supported the task benefits of confirmation, especially challenge. It was found that as coaches call upon student-athletes to refine their skills in a manner that confirms their potential, they become more confident and perceive more cohesion with teammates. This cohesion in turn leads to team winning (i.e., what we term the Communication-Cohesion-Performance Model). This data extends confirmation theory to a novel context and addresses a practical need of sporting practitioners by providing prescriptive advice for leveraging communication to improve team performance.